Many ways to build a polyp - Arendt, Detlev (Trends in genetics, 2019)
The freshwater cnidarian Hydra has been studied for centuries for its unique regenerative capacities. Whole-body single-cell transcriptomics now reveal cellular lineages and gene regulatory networks that build the Hydra polyp. For the first time, transcription factor signatures allow direct comparison of the polyp body plan between Hydra and sea anemone.
Gesehen am 23.03.2020